The new stylized facts about income and subjective well-being - Daniel W. Sacks; Betsey Stevenson; Justin Wolfers (Institute for the Study of Labor (IZA), 2012)
In recent decades economists have turned their attention to data that asks people how happy or satisfied they are with their lives. Much of the early research concluded that the role of income in determining well-being was limited, and that only income relative to others was related to well-being. In this paper, we review the evidence to assess the importance of absolute and relative income in determining well-being. Our research suggests that absolute income plays a major role in determining well-being and that national comparisons offer little evidence to support theories of relative income. We find that well-being rises with income, whether we compare people in a single country and year, whether we look across countries, or whether we look at economic growth for a given country. Through these comparisons we show that richer people report higher well-being than poorer people; that people in richer countries, on average, experience greater well-being than people in poorer countries; and that economic growth and growth in well-being are clearly related. Moreover, the data show no evidence for a satiation point above which income and well-being are no longer related.
Keywords: D6; I3; J1; O1; 330; subjective well-being; life satisfaction; quality of life; Easterlin Paradox; adaptation; economic growth; Zufriedenheit; Einkommen; Lebensqualität; Glücksforschung; Wirtschaftswachstum; Welt